Application Monitoring Design of Water Tank Volume and Clarity System using LabView NI MYRIO - Erwin Nurdiansyah; Chasrun Hasani; Amrul Faruq (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2017)
A traditional controlling and measuring system both in home industry and factory have many constraints especially in the field of quality and efficiency. Operators have to control and monitor while the tank is in the water filling mode. Consequently, an effective system is needed to increase the ease in industry operation. In this work, an application design of water volume in tank and clarity system has presented using RF04 ultrasonic sensor to detect water level; furthermore, a turbidity sensor was also employed to detect water clarity. Both of them were controlled by National Instrument (NI) myRIO-1900. NI myRIO was used in this work as a controller having automatic on/off relay module employed to the water tank and integrated with a personal computer as human machine interface system (HMI). NI LabView software used as HMI in this work was also connected to Wi-Fi module to establish a remote monitoring role. As a result, the simulation shows that water level can be measured utilizing ultrasonic sensor as well as turbidity sensor detection for water clarity.